Prefabrikované základy pod průmyslové zařízení - Šandor, Peter (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Bakalárska práca sa zaoberá návrhom železobetónového základ. Cieľom tejto práce je návrh výšky základu a nadimenzovanie výstuže. Zaoberá sa preklopením a únosnosťou základovej spare. Súčasťou sú taktiež výkresy výstuže výkres tvaru základu.

The bachelor‘s thesis main focus is the design of reinforced concrete foundations. The purpose of this thesis is to design the height of the foundation and the dimensioning of the reinforcements. It also deals with tilting and carrying capacity of the foundation gap. Mechanical drawings of the reinforcements and the shape of the foundation are also part of this thesis
Design of precast foundation for machinery
Keywords: základ; výstuž; železobetón; smyk zaťaženie; kombinácia zaťaženia; dimenzovanie; prepravne úchyty; výkres tvaru; výkres výstuže; foundation; reinforcement; reinforced concrete; skid; load; combinations of loads; reinforcement design; lifting systems; drawing of shape; drawing of reinforcement